2009
DOI: 10.1155/2009/718107
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Microturbine System with Water‐Lubricated Bearings

Abstract: A prototype of the next-generation, high-performance microturbine system was developed for laboratory evaluation. Its unique feature is its utilization of water. Water is the lubricant for the bearings in this first reported application of water-lubricated bearings in gas turbines. Bearing losses and limitations under usage conditions were found from component tests done on the bearings and load tests done on the prototype microturbine. The rotor system using the water-lubricated bearings achieved stable rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The performance of micro thrust and journal bearings is important for the overall performance and dynamic behavior of rotating microengines [1][2][3]. For micro thrust bearing applications, recent research has demonstrated that properly designed texture patterns may substantially increase bearing performance.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of micro thrust and journal bearings is important for the overall performance and dynamic behavior of rotating microengines [1][2][3]. For micro thrust bearing applications, recent research has demonstrated that properly designed texture patterns may substantially increase bearing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient and reliable bearing systems are essential for microrotating machinery, such as micro-motors and micro-turbines [1][2][3]. In micro-thrust bearing applications, liquid lubricants provide increased rotor stability and reduce the probability of solid contact between rotating and stationary parts.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 14 shows rotational speed and temperature rises of lubricant water of the combined bearing. (26), where the distribution ratio of lubricant water and the iron loss are assumed to be 0.45 and 0.2 kW which were deduced from the same kind of generator test [7]. As increasing rotational speed at load rejection brings about an increase of journal bearing loss and churning loss, which depend on rotational speed, the temperature of lubricant water on the antiload side of the thrust bearing increases slightly.…”
Section: Comparison Of Simulation and Measured Resultsmentioning
confidence: 99%
“…Bearing losses are calculated by the governing equations of the water film which are composed of a Reynolds equation for the pressure distribution and an energy equation for the temperature distribution of the water film [7]. The generator rotor is supported by two kinds of bearings.…”
Section: Fig 6 Caicuiation Resuits Of Thrust Bearing and Ciiurning Imentioning
confidence: 99%